2020
DOI: 10.1371/journal.pone.0234988
|View full text |Cite
|
Sign up to set email alerts
|

Quality of care for tuberculosis patients in public health facilities of Debre Tabor town, Northwest Ethiopia

Abstract: Background Even though there are different tuberculosis (TB) prevention and control measures implemented globally including Ethiopia, TB is still major public health problem. This is partly due to compromised quality of care delivered for tuberculosis patients in health facilities (HFs) during diagnosis, treatment and follows-up. Thus this study is intended to determine the quality of care delivered for TB patients in all public HFs of Debre Tabor town, Northwest Ethiopia. Methods Cross sectional study was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
2
7
0
Order By: Relevance
“…e model was widely used in the evaluation of various links of public health service, such as the evaluation of treatment outcomes (outcome), quality of service provision (outcome), and general practitioners training program (process). [29][30][31][32].…”
Section: Evaluation Framework and Indicatorsmentioning
confidence: 99%
“…e model was widely used in the evaluation of various links of public health service, such as the evaluation of treatment outcomes (outcome), quality of service provision (outcome), and general practitioners training program (process). [29][30][31][32].…”
Section: Evaluation Framework and Indicatorsmentioning
confidence: 99%
“…The authors chose not to evaluate the outcome category because of the logistical difficulty of actively seeking people in situations of sexual violence in the health services surveyed, to preserve the privacy of these patients and avoid more distress and possible revictimization [ 11 ]. Researches demonstrated that the Donabedian model is not only a validated approach to assess the safety and quality of a health service [ 12 14 ], but also serves as a basis for auditing [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Ethiopia continues to experience considerable morbidity and mortality from tuberculosis despite the use of various preventive and control strategies; the poor quality of care and treatment given to TB patients in various health facilities (HFs) is one of the contributing reasons [ 2 , 9 , 10 ]. In many resource-limited nations, including Ethiopia, access to high-quality healthcare is a top goal for public health [ 11 ]; however, studies are scarce on the quality of TB care and treatment delivered in public-health facilities in South Wollo zone, Northeast Ethiopia; thus, the present study was conducted to determine the quality of TB care and treatment delivered to TB patients in the study area.…”
Section: Introductionmentioning
confidence: 99%